Novel strategies and therapeutic options for the management of primary biliary cholangitis. (October 2017) - Khanna, Amardeep; Jones, David E.
Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease. It has a varied course of progression ranging from being completely asymptomatic to aggressive disease leading to cirrhosis and resulting in liver transplantation. In addition, symptoms can be debilitating and can have a major impact on quality of life. For decades, there was only one anti-cholestatic agent available to target this disease and that was only effective in around half of patients, with little or no effect on symptoms. With increasing understanding of the pathogenic mechanisms of PBC and potential targets for drug treatment, pharmaceutical companies have shown a greater interest in this rare disease. A large number of novel therapeutic molecules have been developed and are currently being evaluated. In this review article all the novel molecules in use and in trials targeting cholestasis and symptoms in PBC are discussed.